2023
DOI: 10.3390/ijms24021640
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Remodeling of the Blood–Brain Barrier and Neurovascular Unit by Lipopolysaccharide-Induced Neuroinflammation

Abstract: The blood–brain barrier (BBB) is an interface primarily comprised of brain endothelial cells (BECs), separating the central nervous system (CNS) from the systemic circulation while carefully regulating the transport of molecules and inflammatory cells, and maintaining the required steady-state environment. Inflammation modulates many BBB functions, but the ultrastructural cytoarchitectural changes of the BBB with inflammation are understudied. Inflammation was induced in male 8–10-week-old CD-1 mice with intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 52 publications
0
45
0
Order By: Relevance
“…S2 L and M ). Additional ultrastructural analysis using TEM further demonstrates that iKO perilesional microvascular display reduced numbers of macropinocytic vesicles (125 to 300 nm), predominant mediators of BBB disruption through increased transcytosis of plasma ( 23 , 24 ), at 1 dpi ( Fig. 3 I , K , and L ) compared to iWT ( Fig.…”
Section: Resultsmentioning
confidence: 84%
“…S2 L and M ). Additional ultrastructural analysis using TEM further demonstrates that iKO perilesional microvascular display reduced numbers of macropinocytic vesicles (125 to 300 nm), predominant mediators of BBB disruption through increased transcytosis of plasma ( 23 , 24 ), at 1 dpi ( Fig. 3 I , K , and L ) compared to iWT ( Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Previous TEM studies have also found that LPS induces luminal plasma membrane ruffling, a mechanism of non-receptor mediated pinocytosis used by bacteria and viruses to increase infection of epithelial cells (20,42,43). We found a significant increase in severe luminal irregularity in LPS treated mice at ZT13 only (Figure 3A, D).…”
Section: Resultsmentioning
confidence: 91%
“…Intraperitoneal LPS in mice has been shown to induce neuroinflammation, which is characterized by the activation of microglia and astrocytes in the brain [ 19 , 20 ]. Given that the hippocampus is an important organ involved in learning and memory storage in the central nervous system, this study focused on the protective effects of IVIG on the brain and hippocampus.…”
Section: Resultsmentioning
confidence: 99%